2010
DOI: 10.1002/app.33025
|View full text |Cite
|
Sign up to set email alerts
|

Novel whey protein‐based aqueous polymer‐isocyanate adhesive for glulam

Abstract: Whey, a by-product of cheese making, contains whey proteins, lactose, vitamins, and minerals. Whey and whey proteins are still not fully used. In this study, whey protein-based aqueous polymer-isocyanate (API) adhesives were developed and characterized by bond test, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscope (SEM) for bond strength, chemical structures, and morphology. The optimized whey protein-based API adhesive for Glulam had a 28-h boilingdry-boiling wet strength of 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 56 publications
0
60
0
1
Order By: Relevance
“…Therefore, the formation of cellular microstructure should be the key reason that the plywood bonded by DSP/TSP/polyisocyanate adhesive had a cycled bond strength (1.02 MPa) that was just marginally beyond the required value for structural use according to the JIS K6806‐2003 commercial standard. However, polyisocyanate is very reactive to the amino groups of protein . When polyisocyanate was introduced into the DSP/TSP mixture, the crosslinking reactions immediately occurred and formed urea bridges, leading to a rapid increase in adhesive viscosity (as shown in Figure ) or a short work life (∼25–30 min).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the formation of cellular microstructure should be the key reason that the plywood bonded by DSP/TSP/polyisocyanate adhesive had a cycled bond strength (1.02 MPa) that was just marginally beyond the required value for structural use according to the JIS K6806‐2003 commercial standard. However, polyisocyanate is very reactive to the amino groups of protein . When polyisocyanate was introduced into the DSP/TSP mixture, the crosslinking reactions immediately occurred and formed urea bridges, leading to a rapid increase in adhesive viscosity (as shown in Figure ) or a short work life (∼25–30 min).…”
Section: Resultsmentioning
confidence: 99%
“…With increasing consumption of fossil resources, the contradiction between energy supply and demand is becoming more and more prominent. The raw materials of wood adhesive may gradually need to be replaced by renewable biobased polymers, such as soy protein, natural tannins, and starch (Moubarik et al 2009;Gao et al 2011;Wang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…7. It has been confirmed that in a polyisocyanate-protein system, the isocyano groups of polyisocyanate mainly react with residual amino groups rather than the hydroxyl groups of proteins, which is attributed to the much higher reactivity of the isocyano-amino reaction than the isocyano-hydroxyl one (Gao et al, 2011). Some unreacted isocyano groups were detected at 2267 cm −1 , and these could react with the hydroxyl groups of wood to form strong interfacial adhesion via a chemical urethane bridge.…”
Section: Crosslinking Of Soybean Protein With Various Crosslinkersmentioning
confidence: 79%